THE BUMIPUTERA POLICY AND MALAYSIAN BRAIN DRAIN: POLITICS AND BELONGING AS KEY PUSH FACTORS - Masran, Siti Asdiah (Malaysian Journal of International Relations, 2025)
An increasing number of Malaysian professionals are migrating overseas, resulting in a persistent brain drain with profound implications for the nation’s economic development and social cohesion. This paper examines the key push factors driving professional Malaysians to leave their home country, focusing on political inequities, a sense of not belonging, and economic constraints. Using qualitative data from focus group interviews, this study identifies the race-based affirmative action "Bumiputera policy" as a critical factor influencing both Bumiputera and non-Bumiputera professionals. While initially designed to address socioeconomic disparities, these policies have fostered perceptions of inequity, limiting the attachment of skilled Malaysians to their homeland. Despite initiatives like TalentCorp aimed at reversing brain drain, these efforts remain inadequate without systemic reforms. The study contextualises these findings within broader migration theories, offering insights into the interplay between systemic barriers, cultural alienation, and economic dissatisfaction. Policy recommendations include promoting inclusivity, strengthening meritocratic systems, and fostering a unified sense of belonging to curb migration trends.